The role of vitamin D in shoulder health: a comprehensive review of its impact on rotator cuff tears and surgical results - Mohammad Daher; Oscar Covarrubias; Ryan Lopez; Peter Boufadel; Maria Catherine Rita Hachem; Ziad Zalaquett; Mohamad Y. Fares; Joseph A. Abboud (Clinics in Shoulder and Elbow)
Vitamin D deficiency is highly prevalent in the general population and is associated with various chronic health conditions. In addition to its role in bone mineralization, Vitamin D has various physiological effects that may impact the pathogenesis of shoulder pathologies. Vitamin D deficiency may also affect outcomes after shoulder surgeries, such as rotator cuff repair and total shoulder arthroplasty. Vitamin D plays a role in tissue healing, bone growth, and maintenance of homeostasis in skeletal muscle cells. Vitamin D also has anti-inflammatory effects that are important to rotator cuff health. Vitamin D deficiency is highly prevalent in patients with rotator cuff tears, suggesting its role as a potential risk factor. Vitamin D deficiency has been associated with decreased preoperative shoulder strength as well as increased retear rates, postoperative stiffness, and the need for revision surgery in patients who underwent rotator cuff repair. Studies have also demonstrated a potential association between vitamin D deficiency and increased risk of revision after total shoulder arthroplasty. Further research is necessary to elucidate the direct role of vitamin D in the pathogenesis of rotator cuff tears and its impact on clinical outcomes after rotator cuff surgery and total shoulder arthroplasty.